Using a tele-behavioral health rapid intake model to address high demand for psychotherapy at an academic medical center during COVID-19 - McMahan, Kristina; Martin, Karli M.; Greenfield, Melissa J.; Hay, Pamela; Bates Redwine, Madison; Fargason, Rachel; Lokken, Kristine (Frontiers in Psychiatry, 2022)
Background: Long wait times for mental health appointments have been a chronic dilemma for academic medical centers. This problem intensified worldwide with the onset of the COVID-19 pandemic. Wait times for mental health appointments also increased, varying across populations from 3 to 18 months. As prolonged wait time is positively associated with severity of psychiatric symptoms and negative outcomes, the authors implemented a novel rapid intake telemedicine clinic model to shorten wait time and increase patient access to psychological care at an academic medical center. Methods: To address an overwhelming influx of mental health referrals and a growing wait-time-until-first appointment at an academic medical center serving as a lone safety net hospital during the COVID-19 pandemic, a 5-provider Psychology Rapid Intake Team was established using a hybrid of telehealth and in-person appointments. Data on new patient volumes, wait time for 1st appointment, and wait time to begin therapeutic intervention were compared during the same calendar 3-month period immediately prior to and following implementation of the rapid intake clinic. Results: A paired-samples t-test was conducted to compare new patient volumes pre- versus post- intervention. Results revealed a significant increase in the number of new patients the providers were able to accommodate in the post-implementation (M = 62.00, SD = 7.21) compared to the pre-implementation (M = 31.00, SD = 2.61) condition; t(2) = -8.60, p < .05. There was a significant decrease in the average wait times for 1st appointment post-implementation (M = 24.99, SD = 2.38) compared to the pre-implementation (M = 37.32, SD = 1.47) condition; t(2) = 5.56, p < .05. In addition, days to begin therapeutic intervention decreased dramatically (394%) from the pre- (M = 142.50) to post-implementation (M = 28.84) period. Conclusions: The COVID-19 pandemic strained a mental healthcare system which led to increasingly long wait times for intake appointments and delayed psychotherapy interventions. The PRIT initiative served to improve access, reduce patient risk related to prolonged wait times, and accelerated patient engagement with psychotherapy services. The model can serve as a unique, sustainable infrastructure for behavioral health delivery in large health care systems.